1985
DOI: 10.1159/000215140
|View full text |Cite
|
Sign up to set email alerts
|

On the Retraction of Collagen and Fibrin Induced by Normal, Defective and Modified Platelets

Abstract: Fibrin clot retraction (FCR) and collagen gel retraction (CGR) were studied in patients with inherited platelet defects, i.e. in Glanzmann’s thrombasthenia, Hermansky-Pudlak syndrome, May-Hegglin anomaly, giant platelet syndrome, as well as in patients with von Willebrand disease and factor XIII deficiency. FCR was abnormal only in thrombasthenia, while CGR was found to be reduced in 2 patients with Hermansky-Pudlak syndrome and in 4 out of 5 cases with von Willebrand disease. Both FCR and CGR were normal in M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…The role of platelet FXIII in clot retraction is not clear. Platelet clot retraction of FXIII-deficient patients was found to be normal (162,306) or even enhanced (274). In contrast, reduced contractile force was measured in plateletrich plasma clot from a FXIII-deficient patient (57), and the combination of FXIII-A-deficient plasma with normal platelets was sufficient to impair isometric contraction of platelet-rich plasma clot (66).…”
Section: A Involvement Of Factor XIII In Platelet Functionmentioning
confidence: 99%
“…The role of platelet FXIII in clot retraction is not clear. Platelet clot retraction of FXIII-deficient patients was found to be normal (162,306) or even enhanced (274). In contrast, reduced contractile force was measured in plateletrich plasma clot from a FXIII-deficient patient (57), and the combination of FXIII-A-deficient plasma with normal platelets was sufficient to impair isometric contraction of platelet-rich plasma clot (66).…”
Section: A Involvement Of Factor XIII In Platelet Functionmentioning
confidence: 99%
“…Aside from altering the structure of the fibrin network, a possible role of fibronectin in blood clots is to mediate interactions between cells or platelets and fibrin. Thus, fibronectin as well as fibrin may interact with platelet α IIb β 3 during clot retraction, a function that is deficient in Glanzmann's thrombasthenia [41]. Fibrin cross‐linked to fibronectin by FXIIIa (fibronectin–fibrin) constitutes a three‐dimensional matrix that increases adhesion and spreading of fibroblasts compared with fibrin alone [42].…”
Section: Fibronectin and Blood Coagulationmentioning
confidence: 99%
“…5,6 In particular, platelets cause clot retraction (CR) by retracting extended filopodia along fibrin strands. 7 There have been conflicting reports about the effects of FXIII deficiency on CR; investigators reported that the absence of FXIII abolished, 7-9 did not affect, 10,11 or rather enhanced 12 CR in patients with congenital FXIII deficiency. However, platelet aggregation induced by various agents is uniformly normal in patients with congenital FXIII deficiency.…”
Section: Introductionmentioning
confidence: 99%